A4_2 Life is a Highway - Paton, Charlotte; Thomas, Kaia; Wing, Matthew; McCabe, Nat (Physics Special Topics, 2021)
In this paper we examine the distance that an individual would travel around the Universe in their lifetime, based off of the popular song “Life is a Highway”. To do this, the distance of an Earth orbit around the Sun was calculated. Further to this, the orbit of the Solar System around the centre of the Milky Way and the movement of the Galaxy through space were also considered. The average life expectancy of a person was set to 80.7 years and, from this, the total distance a person would travel is found to be 2.12 × 10^15 km.